1975
DOI: 10.1073/pnas.72.8.2950
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of elongation factor Tu with 2'(3')-O-aminoacyloligonucleotides derived from the 3' terminus of aminoacyl-tRNA.

Abstract: The interaction between Escherichia coli elongation factor-Tu-GTP complex and chemically synthesized 2'(3')-O-aminoacyldinucleoside phosphates with the nucleotide sequence of the 3' terminus of aminoacyl-tRNA (AA-tRNA) has been studied. It was found that C-A-Phe, C-A-Pro, and C-A-Asp interact with EF-Tu-GTP, causing the release of GTP bound to the enzyme. The specificity of this interaction closely resembles that of AA-tRNA since C-A and C-A(Ac-Phe) as well as the corresponding tRNAs are inactive. The 3'-O-ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

1976
1976
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…The same phenomenon has been observed withE. coli EF-Tu-GTP complex and chemically synthesized 2'(3')-O-aminoacyldinucleotide phosphates (CpA-Phe, CpA-Pro, and CpA-Asp) with the nucleotide sequence of the 3'-terminus of aminoacyl-tRNA (26). We did not examine if the released GTP was hydrolyzed, but in the case of GTP release by interaction with the aminoacyldinucleotides no hydrolysis of GTP has been detected (S.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The same phenomenon has been observed withE. coli EF-Tu-GTP complex and chemically synthesized 2'(3')-O-aminoacyldinucleotide phosphates (CpA-Phe, CpA-Pro, and CpA-Asp) with the nucleotide sequence of the 3'-terminus of aminoacyl-tRNA (26). We did not examine if the released GTP was hydrolyzed, but in the case of GTP release by interaction with the aminoacyldinucleotides no hydrolysis of GTP has been detected (S.…”
Section: Discussionsupporting
confidence: 74%
“…1). This is lower than the interaction with authentic aminoacyl-tRNA (stoichiometry of 1:1) but is considerably more effective than the reaction with 2'-O-aminoacyldinucleotides (26).…”
Section: ~~~~~~õmentioning
confidence: 82%
“…Phe-tRNAPhe-C-C-37NH2A shows no activity in the EF-Tu dependent binding to E. coli ribosomes (Sprinzl et al, 1975). It was suggested recently that, during the interaction of aminoacyl-tRNA with the elongation factor Tu, the amino acid is linked to the 27-hydroxyl group of the terminal adenosine (Ringer and Chládek, 1975). Our results, however, disprove this hypothesis for the eukaryotic system.…”
Section: Experiments In Tablesupporting
confidence: 52%
“…It is interesting to note that similar differences between various aminoacyl derivatives (Figure la-c) were observed in the nonribosomal kirromycin-dependent system (Bhuta & Chládek, 1980) and, also, in the formation of ternary AA-tRNA-EF-Tu-GTP complexes with AA-tRNAs differing in the aminoacyl residues (Pingoud & Urbanke, 1980;Wagner & Sprinzl, 1980; Knowlton & Yarus, 1980). Further, it was shown that C-A-Phe interacts more strongly with EF-TU-GTP than do C-A-Asp or C-A-Pro (Ringer & Chládek, 1975) and that C-A-Phe protected EF-TU against the sulfhydryl reagent more effectively than did C-A-Leu (Jonák et al, 1980). These results are well supported by the literature pertinent to the interaction of intact AA-tRNA with EF-TU (see above) but are difficult to reconcile with the claim of Parlato et al (1981) that the nature of the aminoacyl residue of the effector (3'-terminal fragments of AA-tRNA) does not significantly influence EF-Tu-GTPase in the presence of kirromycin.…”
Section: Resultsmentioning
confidence: 99%